Towards an Online Programming Platform Complementing Software Engineering Education - Niels Gandraß and Torge Hinrichs and Axel Schmolitzky (CEUR workshop proceedings, 2020)
Existing online programming platforms provide many opportunities for individuals to develop and improve their programming skills. Using descriptive assignments that address different skill levels these platforms target both beginners and experienced programmers. We used one such platform featuring advanced exercises in a project course during the fifth semester of our bachelor degrees in computer science and were surprised by its success and the high motivation of the participants. Nonetheless, we also observed deficits of the platform with regard to software engineering aspects. In this paper we identify requirements for an online programming platform that complements software engineering education and match existing platforms against these proposed requirements.
Keywords: education; online assessment; online programming platform; programming; software engineering education; team programming